Sexual Dimorphism in the Association of Serum Retinol-Binding Protein-4 With Long-Term Dynamic Metabolic Profiles in Non-Diabetes - Xiang, Jiali; Dai, Huajie; Hou, Yanan; Wang, Qi; Wang, Tiange; Li, Mian; Zhao, Zhiyun; Lu, Jieli; Dai, Meng; Zhang, Di; Xu, Yu; Ning, Guang; et al. (Frontiers in Endocrinology, 2022)
Objectives: We aimed to investigate the association of circulating retinol-binding protein-4 (RBP4) levels with long-term cardiometabolic risk profiles and whether sex disparity mattered. Methods: We included 784 non-diabetic participants aged 40 years and above from a well-defined community-based cohort at baseline in 2005 and were invited to attend the on-site follow-up examination for two consecutive times with 3-year interval in 2008 and 2011 respectively. Serum RBP4 were measured at baseline, and the anthropometry and biochemical measurements were performed at each visit. Generalized Estimating Equations models were used to assess the association of serum RBP4 levels with the dynamic changes in adiposity and glucolipid profile. Results: Based on all the baseline and the 3- and 6-year of follow-up data, baseline serum RBP4 levels (each 1-uinit of log10RBP4) were significantly associated with waist circumference (β=3.12, 95% confidence interval [CI] [0.77, 5.47], P=0.01), fasting and 2h post-loading glucose (β=0.26 [0.05, 0.47], P=0.02, and 1.70 [1.29, 2.12], P< 0.0001), serum triglycerides (β=0.75, 95% CI [0.54, 0.96], P< 0.0001), total cholesterol (β=0.47, 95% CI [0.23 0.70], P<0.0001), and marginally with body mass index (β=0.97, 95% CI [0.02, 1.93], P=0.046), in total participants, after adjusting potential confounders. The association of RBP4 with 2h post-loading glucose was stronger in women than that in men (β=1.99, 95% CI [1.49, 2.50] vs. 0.61 [-0.14, 1.36], P for interaction=0.001). The analysis of change in Z-score of cardiometabolic profiles corresponding to each 1-unit increment in log10RBP4 showed consistent results. Conclusions: Higher RBP4 levels are associated with longitudinal increase in adiposity and deteriorated glucolipid profile defined by repeated measurements. The associations differ in sex regarding to the 2h post-loading glucose.